2008
DOI: 10.1038/sj.ijo.0803710
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the effects of dietary counseling on gestational weight gain and glucose metabolism in obese pregnant women

Abstract: Objective: Can gestational weight gain in obese women be restricted by 10-h dietary consultations and does this restriction impact the pregnancy-induced changes in glucose metabolism? Design: A randomized controlled trial with or without restriction of gestational weight gain to 6-7 kg by ten 1-h dietary consultations. Subjects: Fifty nondiabetic nonsmoking Caucasian obese pregnant women were randomized into intervention group (n ¼ 23, 2874 years, prepregnant body mass index (BMI) 3574 kg m À2 ) or control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
553
5
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(580 citation statements)
references
References 25 publications
11
553
5
11
Order By: Relevance
“…[19][20][21][22] Lifestyle interventions have the potential to help women gain the recommended amount of weight, [23][24][25][26][27] through behavioral strategies, dietary intake recommendations and physical activity. The current research aims to identify sociodemographic and health characteristics of those at elevated risk for excessive gestational weight gain according to the updated 2009 IOM guidelines, with a particular focus on potential racial/ethnic disparities.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Lifestyle interventions have the potential to help women gain the recommended amount of weight, [23][24][25][26][27] through behavioral strategies, dietary intake recommendations and physical activity. The current research aims to identify sociodemographic and health characteristics of those at elevated risk for excessive gestational weight gain according to the updated 2009 IOM guidelines, with a particular focus on potential racial/ethnic disparities.…”
Section: Introductionmentioning
confidence: 99%
“…All of these may have contributed to the large heterogeneity in the findings. Interestingly, a few studies found an improvement in glucose tolerance in the intervention group, even if no reduction was seen in the risk of GDM [46][47][48].…”
mentioning
confidence: 99%
“…To date, existing interventions to prevent excessive weight gain are so limited in number and effectiveness, that both the IOM [32] and the Agency for Health care Research and Quality (AHRQ) [33] have identified this as a major research gap. Interventions based on physical activity and dietary counseling, usually combined with supplementary weight monitoring [34,35], have had modest success in reducing the amount of excessive weight gained during pregnancy, but few efforts have been effective enough for women to gain within their IOM target range [36,37]. Thus, we need to design effective interventions that prevent excessive weight gain during pregnancy that are widely effective, practical, cost-effective, and have mechanisms for widespread diffusion.…”
Section: Shifting Perspectivesmentioning
confidence: 99%